Dual random optimized pulse width modulation controller for three-phase voltage source inverter driven brushless DC motor - Halidu Abdul Mumin; Solomon Nunoo; Joseph Cudjoe Attachie (Institute of Advanced Engineering and Science, 2026)
Brushless DC (BLDC) motors are widely employed in modern power electronic applications due to their high efficiency and dynamic performance. However, conventional pulse width modulation (PWM) techniques often generate concentrated harmonic components, leading to acoustic noise, torque ripple, and reduced inverter efficiency. This paper proposes an artificial neural network–assisted dual random pulse width modulation (ANN-DRPWM) strategy to enhance the output quality of a three-phase voltage source inverter driving a BLDC motor. In the proposed approach, supervised ANN training enables dual randomization of the carrier and modulation signals, effectively dispersing harmonic energy while maintaining improved DC-link voltage utilization. A passive LC filter is subsequently integrated to further suppress residual harmonics and ensure compliance with harmonic standards. The system is modeled and simulated in MATLAB/Simulink and evaluated against conventional sinusoidal PWM and flying capacitor multilevel inverter (FCMLI) techniques. Results demonstrate that the proposed ANN-DRPWM method achieves a post-filter total harmonic distortion (THD) of 2.17%, along with a 6-9% improvement in inverter efficiency and a noticeable reduction in torque ripple. Overall, the proposed strategy offers an efficient and intelligent modulation solution for high-performance BLDC motor drives, suitable for applications such as electric vehicles, renewable energy systems, and industrial drives.